Peningkatan Kapasitas Pelaku Usaha melalui Pelatihan Akuntansi dan Pajak UMKM di Desa Bira - Azisah, Andi Nurul; Muflikhah, Itsna; Br. Ginting, Chris Dayanti; Surianto, Nurul Maghfirah; Jauhari, Yustika (Department of Accounting, Faculty of Business and Economics, Universitas Islam Indonesia, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in the economic life of rural communities; however, many business actors still face challenges in maintaining business financial records and understanding tax obligations. This condition was also found among MSME actors in Bira Village, Bontobahari District, Bulukumba Regency, where business owners generally had not recorded transactions in an orderly manner and had not separated business finances from household finances. This community service activity aimed to improve the basic understanding and skills of MSME actors through simple accounting training and MSME tax education. The activity was carried out using an educational and participatory approach, beginning with an initial identification stage through observation, coordination with the village government, and discussions with participants, followed by material delivery, question-and-answer sessions, and direct practice in preparing simple financial records. The evaluation was conducted through oral questions and answers at the beginning and the end of the activity, as well as observation during the practice session. The results showed that participants gained a better understanding of the importance of transaction recording, the separation of business and personal finances, and the relationship between financial recordkeeping and MSME tax administration. This activity had a positive impact in the form of improved initial understanding, basic business recordkeeping skills, and increased awareness of the importance of more orderly and sustainable business management.